2020
DOI: 10.1186/s13012-020-00998-w
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of training methods for delivery of evidence-based psychotherapies: a systematic review

Abstract: Background Extensive efforts have been made to train mental health providers in evidence-based psychotherapies (EBPs); there is increasing attention focused on the methods through which providers are trained to deliver EBPs. Evaluating EBP training methods is an important step in determining which methods are most effective in increasing provider skill and improving client outcomes. Methods We searched MEDLINE (Ovid) and PsycINFO for randomized con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 58 publications
4
40
0
Order By: Relevance
“…One recent review of training effectiveness excluded studies in which the majority of those trained did not have advanced degrees 75 . Another recent review of training effectiveness found that half of the included studies included trainees or unlicensed individuals, but did not specify educational levels of participants 76 . All providers, regardless of experience, likely need some level of ongoing support to continue delivering EBTs with high fidelity 73,75‐77 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One recent review of training effectiveness excluded studies in which the majority of those trained did not have advanced degrees 75 . Another recent review of training effectiveness found that half of the included studies included trainees or unlicensed individuals, but did not specify educational levels of participants 76 . All providers, regardless of experience, likely need some level of ongoing support to continue delivering EBTs with high fidelity 73,75‐77 .…”
Section: Discussionmentioning
confidence: 99%
“…Sustainment studies typically focus on whether the EBT is still in use, with more research needed to understand how to maintain fidelity and delivery quality over long periods of time 68‐73 . It is possible that individuals with less mental health training and experience prior to EBT training may need more ongoing supervision than those with advanced degrees, or may differ in the benefits they receive from different training and supervision approaches 10,40,74‐77 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It remains an unfortunate truth that methods for training therapists to implement EBIs in usual care have not produced substantial impacts on EBI adoption, delivery, or quality (Beidas et al, 2019;Valenstein-Mah et al, 2020). Perhaps teaching therapists to be more reliable and accurate coders of EBI techniques can yield benefits that are cognitive (e.g., increased knowledge of EBI techniques and when they can be used), attitudinal (e.g., stronger confidence and motivation to use EBIs), and/or behavioral (e.g., enhanced capability to deliver EBIs via observational modeling and instrumental learning) in nature (McLeod et al, 2018).…”
Section: Potential Next Steps In Therapist Coder Trainingmentioning
confidence: 99%
“…Manualized EBIs use standardized clinician training protocols, often in conjunction with ongoing expert consultation and provider certification procedures, to ensure high-fidelity model delivery and continuous quality improvement. Yet, over three decades of research show that whereas EBI training and consultation can increase EBI satisfaction and immediate skill acquisition among community practitioners, they do not reliably or appreciably increase practitioner use of EBIs with their clients, especially after interactions with experts cease (Beidas et al, 2019;Valenstein-Mah et al, 2020). Moreover, training and quality procedures for manualized EBIs can be prohibitively costly and resource-intensive to sustain in everyday care.…”
Section: Introductionmentioning
confidence: 99%